2019
DOI: 10.3390/foods8050178
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Distrust about E-numbers: A Qualitative Study among Food Experts

Abstract: Food additives (E-numbers) are allowed in foods, but many consumers have a negative perception of them. The objective was to study the opinion of food experts about the causes and ways to reduce consumer distrust about E-numbers. Thirteen food experts from universities, research institutes, the government, food industry organisations, media, a nutrition information organisation, a consumer association and two other non-governmental organisations (NGOs) were interviewed with a semi-structured topic list, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…Subthemes within this theme also gave the responsibility for sugar and sweetener consumption to governments and the food industry, and permitted an even further reduced role for the individual through ideas of ‘deception’. Previous research has also revealed this blame towards external organizations [ 12 , 13 , 15 , 17 , 18 , 19 , 23 , 57 ], and this distrust in health professionals, government agencies, and in the food industry [ 13 , 16 , 23 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subthemes within this theme also gave the responsibility for sugar and sweetener consumption to governments and the food industry, and permitted an even further reduced role for the individual through ideas of ‘deception’. Previous research has also revealed this blame towards external organizations [ 12 , 13 , 15 , 17 , 18 , 19 , 23 , 57 ], and this distrust in health professionals, government agencies, and in the food industry [ 13 , 16 , 23 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire consists of questions on the knowledge of biopreservatives to investigate the awareness about the preservatives. Some of these questions contained definitions from the EU Regulation, which indirectly allowed us to evaluate whether the legislation is understandable for the consumer or if there is an actual lack of clarity from the regulatory point of view, as highlighted on more than one occasion in the literature about novel food products or technologies [37][38][39]. In particular, the focus of the investigation was on consumer knowledge of the definition of preservative and the difference between natural and synthetic preservatives.…”
Section: Methodsmentioning
confidence: 99%
“…Although food additives are useful ingredients in the food industry, with some benefits for consumers, being strictly regulated by governmental authorities, the rejection of their presence in food is increasing in the last decades (Szűcs et al, 2019;van Gunst & Roodenburg, 2019). On the Netherlands, food experts indicated that low reliability in the food industry and preponderance of negative information about food additives on the internet and social networks are the main causes of high risk perception (van Gunst & Roodenburg, 2019). The authors stated that forms of communication with the public, including labeling, need to be improved to overcome this barrier and increase acceptance of these substances.…”
Section: Food Additivesmentioning
confidence: 99%